Α4β7high CD4+ T cells are prone to be infected by HIV‐1 and associated with HIV‐1 disease progression. (15th March 2022) - Mijiti, Zilaiguli; Song, Jin‐Wen; Jiao, Yan‐Mei; Gao, Lin; Ma, Hai‐Mei; Guo, Xiao‐Yan; Zhang, Qing; Guo, Yun‐Tian; Ding, Jian‐Bing; Zhang, Shi‐bin; Wang, Fu‐Sheng
Abstract: Introduction: To investigate the characteristics of β7 high CD4 + T cells during HIV‐1 infection and the relationship between β7 high CD4 + T cells and HIV‐1 disease progress. Methods: This study enrolled 124 HIV‐1‐infected patients, including 80 treatment naïve patients (TNs), 41 patients who underwent antiretroviral therapy (ARTs), and three long‐term no progression patients (LTNPs). Nineteen matched healthy subjects were included as controls (HCs). The characteristics and frequency of β7 high CD4 + T cells were analyzed using flow cytometry. An in vitro culture experiment was used to study HIV‐1 infection of β7 high CD4 + T cells. Real‐time polymerase chain reaction was performed to quantify HIV‐1 DNA and CA‐RNA levels. Results: The frequency of β7 high CD4 + T in the peripheral blood was significantly decreased and negatively correlated with disease progression during chronic HIV‐1 infection. A large proportion of β7 high CD4 + T cells showed Th17 phenotype. Furthermore, β7 high CD4 + T cells were preferentially infected by HIV‐1 in vitro and in vivo. There were no significant differences of HIV‐1 DNA, and CA‐RNA levels between β7 high CD4 + T and β7 low CD4 + T subsets in HIV‐1 infected individuals after antiviral treatment. Conclusion: The β7 high CD4 + T cells were negatively correlated with disease progression during chronic HIV‐1 infection. β7 high CD4 + T cells are susceptible to infection with HIV‐1 and HIV‐1 latent cells.